Agw 710 Consultancy Focus Fine Engineering Sdn Bhd - Khor, Boon Hou; Chong, Chee Hui; Tahir, Mohd Subri; Abd Razak, Ahmad Zainal Abidin (Universiti Sains Malaysia, 2009)
In Malaysia, the small business sector has been accepted as an important contributor to the nation's overall wealth and a major source of jobs as it was in many other countries. However, Small Medium Ent rprise (SME) contribution to the economy is still comparatively insignificant. Therefore, the Malaysian Government has made the development of SMEs a high priority area, especially those with high growth and export potential. This is indicated in the national development agendas, namely the Ninth Malaysia Plan (9MP) and the Third Industrial Master Plan (IMP3 ), in which the key strategies for SME development is outlined for the 2006-2010 and 2006-2015 periods respectively (Bank Negara report 2007).